Waist Circumference and Objectively Measured Sedentary Behavior in Rural School Adolescents. (January 2016) - Machado‐Rodrigues, Aristides M.; Coelho e Silva, Manuel J.; Ribeiro, Luís P.; Fernandes, Romulo; Mota, Jorge; Malina, Robert M.
ABSTRACT: BACKGROUND: Research on relationships between lifestyle behaviors and adiposity in school youth is potentially important for identifying subgroups at risk. This study evaluates the associations between waist circumference (WC) and objective measures of sedentary behavior (SB) in a sample of rural school adolescents. METHODS: The sample included 254 students (114 boys, 140 girls), 13‐16 years of age, from rural regions of the Portuguese midlands. Height, weight, and WC were measured. Cardiorespiratory fitness (CRF) was assessed with the 20‐m shuttle‐run test. An uniaxial GT1M accelerometer was used to obtain 5 consecutive days of physically activity (PA) and SB. Multiple linear regression was used to test associations between WC and SB, adjusted for several potential confounders (age, sex, PA, CRF, parental education). RESULTS: SB was not significantly associated with the WC, neither in the unadjusted model nor after adjustment for all potential confounders. In the final model, the unique significant predictor of the WC was cardiorespiratory fitness (β = −0.82; 95% confidence interval [CI], −1.02 to −0.62). CONCLUSION: WC was not independently associated with SB time in rural school adolescents. Future research is claimed among rural adolescents in different geographic contexts to try to clarify recent findings of less studied communities.